ASSESSING THE IMPACT OF INNOVATION-DRIVEN DEVELOPMENT ON MACROECONOMIC INDICATORS USING PANEL DATA MODELS (Regional aspects of productive forces development of Ukraine, 2026)
Introduction. In the contemporary global economy, innovation-driven development is a key determinant of long-term economic growth, as intellectual capital, technological knowledge, and their commercialization largely shape the competitiveness of national economies. International experience demonstrates that countries which systematically invest in research and development, human capital formation, and institutional support for innovation achieve higher rates of labour productivity growth and socio-economic resilience. For Ukraine, this issue is particularly relevant in the context of post-crisis recovery and integration into the European research and innovation area, given the presence of substantial scientific potential alongside a persistently low level of innovation commercialization.Purpose of the study. The purpose of the study is to identify and quantitatively assess the impact of key innovation factors on Ukraine’s economic growth in comparison with European Union countries and Central and Eastern European states over the period 2010–2024, using dynamic panel data models.Methods. The study combines theoretical, statistical, and econometric methods. The theoretical framework is based on the endogenous growth theory. The empirical analysis relies on a panel dataset covering 11 countries for the period 2010–2024, incorporating indicators of research and development expenditure, patent activity, human resources in research, high-technology exports, and the Global Innovation Index.Results. The results confirm a statistically significant positive impact of innovation factors on economic growth rates across the sample countries. Research and development expenditure, the Global Innovation Index, and high-technology exports are identified as the most influential growth determinants. The analysis reveals the presence of temporal inertia in innovation effects, whereby investments in science and increases in patent activity affect economic dynamics with a lag of one to two years. The comparative analysis indicates that Ukraine possesses considerable innovation potential but lags behind EU countries in its realization due to limited funding, institutional imbalances, and the outflow of highly qualified human capital.Prospects. The findings may be used to substantiate priorities of Ukraine’s state innovation policy, particularly with regard to long-term stimulation of investment in research and development, increased private sector involvement, and deeper integration of the national innovation system into the European research and innovation area. The proposed methodological approach provides a basis for further research on innovation-driven development and economic growth forecasting.Keywords: innovation-driven development; economic growth; research and development; technological change; econometric modelling; panel data; innovation policy; competitiveness; sustainable development.Formulas: 0, fig.2: 0, tabl.: 0, bibl.: 17.